Indonesia's Political and Economic Relations with the Soviet Union in 1959-1965 - Marwanti, Emi; Hidayat, Bobi; Hartati, Umi; Ramli, Arwin (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The purpose of this research is to explains the background to the political and economic relations between Indonesia and the Soviet Union, relations between Indonesia and the Soviet Union and describe the economic relations between Indonesia and the Soviet Union in 1959-1965. Describe the impact and political relations between Indonesia and the Soviet Union during the guided democracy period of 1959-1965. This research method uses detailed historical research and data collection stages, namely by collecting data through documentation studies and literature studies, carrying out data validity by testing or carrying out internal and external criticism of data sources, interpreting data, namely providing comments or conclusions on each quote, and writing. report (historiography) using Indonesian.The results of the research show that (1) The background to the establishment of relations between Indonesia and the Soviet Union was a form of concern and also for the sake of gaining allies, the Soviet Union had the initiative to support the sovereignty of the Indonesian State by discussing it at the UN forum (2) Political relations were established through cooperation in the field of military. (3) Economic cooperation relations in the form of loans and trade, (4) Political-economic impacts and relations are the forerunners of the Non-Aligned movement. economic development of the country, and increasing trade activities.